Poziţionarea entităţii jurământului în cadrul epistemologiei dreptului muncii din Republica Moldova [Articol] - Sadovei, Nicolae (My University, 2012)
In the present article, the author approaches the entity of taking an oath in the framework of epistemology of the Labour Law of the Republic of Moldova in the context in which, holding certain functions, over 20 categories of natural persons, in staff-service, according to the law have the obligation to take an oath. Thus, the juridical reports of the respective work, which appear in the result of taking up the post, are reports conditioned by the taking of the oath. In the situation when the legal obligation of taking the oath in order to take up a position is rising, it is absolutely necessary to work out a well grounded concept of the act of taking the oath, to comprise all the juridical aspects of the given entity, including the aspect of the mix juridical nature of the given act.